Scientific evidence on the pattern of alcohol consumption by health professionals in the oncological context (Research, Society and Development, 2022)
Objective: To describe scientific evidence on the pattern of alcohol consumption by health professionals in the oncological context, focusing on supporting the research object of a doctoral study on 'alcohol consumption by members of the nursing team working in an oncology hospital'. Methodology: Integrative literature review guided by the acronym PICo (Participant, Phenomenon of Interest and Context). For the literature review, the scientific databases LILACS, CINAHL, BDENF, MEDLINE and Web of Science were adopted with the aforementioned search strategies and time frame from 2010 to 2021. The survey was limited to articles published in Portuguese, English and Spanish, excluding review articles, dissertations and theses. Results: Seven articles were selected, of which six (85.7%) addressed the pattern of alcohol consumption among the nursing team and one (14.3%) addressed the pattern of alcohol consumption among health professionals. Conclusion: Based on the references found, it is noteworthy that the study on the pattern of consumption of alcoholic beverages by health professionals working in the oncological scenario has not yet been explored. The search did not retrieve any study carried out in Brazil with the proposed theme. This puts the need to invest in research in the area of ​​workers' health that address the pattern of consumption of alcoholic beverages by health professionals, especially nurses.